Selenium speciation in seleniferous agricultural soils under different cropping systems using sequential extraction and X-ray absorption spectroscopy. (June 2017) - Qin, Hai-Bo; Zhu, Jian-Ming; Lin, Zhi-Qing; Xu, Wen-Po; Tan, De-Can; Zheng, Li-Rong; Takahashi, Yoshio
Abstract: Selenium (Se) speciation in soil is critically important for understanding the solubility, mobility, bioavailability, and toxicity of Se in the environment. In this study, Se fractionation and chemical speciation in agricultural soils from seleniferous areas were investigated using the elaborate sequential extraction and X-ray absorption near-edge structure (XANES) spectroscopy. The speciation results quantified by XANES technique generally agreed with those obtained by sequential extraction, and the combination of both approaches can reliably characterize Se speciation in soils. Results showed that dominant organic Se (56–81% of the total Se) and lesser Se(IV) (19–44%) were observed in seleniferous agricultural soils. A significant decrease in the proportion of organic Se to the total Se was found in different types of soil, i.e., paddy soil (81%) > uncultivated soil (69–73%) > upland soil (56–63%), while that of Se(IV) presented an inverse tendency. This suggests that Se speciation in agricultural soils can be significantly influenced by different cropping systems. Organic Se in seleniferous agricultural soils was probably derived from plant litter, which provides a significant insight for phytoremediation in Se-laden ecosystems and biofortification in Se-deficient areas. Furthermore, elevated organic Se in soils could result in higher Se accumulation in crops and further potential chronic Se toxicity to local residents in seleniferous areas. Highlights: The combination of sequential extraction and XANES technique can quantify reliably Se speciation in seleniferous soils. Se in seleniferous agricultural soils was primarily in the form of organic Se along with lesser amounts of Se(IV). Organic Se in seleniferous soils was likely derived from plant litter. Se speciation in seleniferous agricultural soils was influenced by different cropping systems. Abstract : Se in seleniferous agricultural soils was primarily in the form of organic Se along with lesser Se(IV), and soil Se speciation was influenced by different cropping systems.